Penentuan Lokasi dan Kapasitas Kapasitor Bank pada Jaringan Distribusi Penyulang Americano untuk Meminimalkan Rugi-Rugi Daya dengan Metode Grey Wolf Optimizer (GWO) - banjar nahor, kevin elvredo; Zebua, Osea; Hakim, Lukmanul (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2023)
The installation of capacitor banks is one way to reduce power losses and increase the voltage profile. Banks capacitor will supply capacitive reactive power, so that the impedance value can be reduced resistance. The increase in resistance leads to a decrease in the voltage profile and an increase in power reduction. Based on data from the simulation experiment with software ETAP 19.01, the highest decrease in voltage profile in Americano feeder at daylight load was 4.1 kV with total power losses of 449.5 kW and during night loads of 6 kV with total power losses of 917 kW. Based on this, the adding of capacitor banks is carried out using the Gray Wolf Optimizer (GWO) method to help the process of finding the location and capacity of capacitor banks. Decrease in active power loss after installing the capacitor bank during daytime loads was 148.5 kW, with an increase in the average voltage of 1,212 kV and during night loads was 374 kW, with an increase in the average voltage of 1.46 kV. Determining the location and capacity of the capacitor bank, the value of the power decrease and the maximum voltage profile increase are obtained.